2013
DOI: 10.1371/journal.pone.0065719
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Olanzapine and N-desmethyl-olanzapine in Plasma Using a Reversed-Phase HPLC Coupled with Coulochemical Detection: Correlation of Olanzapine or N-desmethyl-olanzapine Concentration with Metabolic Parameters

Abstract: BackgroundOlanzapine (OLZ) is one of the most prescribed atypical antipsychotic drugs but its use is associated with unfavorable metabolic abnormalities. N-desmethyl-olanzapine (DMO), one of the OLZ metabolites by CYP1A2, has been reported to have a normalizing action on metabolic abnormalities, but this remains unclear. Our aim was to explore the correlation between the concentrations of OLZ or DMO with various metabolic parameters in schizophrenic patients.MethodsThe chromatographic analysis was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
15
0
2
Order By: Relevance
“…Another cross-sectional study revealed no significant difference in Hcy level between schizophrenia patients receiving clozapine in monotherapy and healthy controls (Wysokiński and Kłoszewska, 2013 ). There is also one study showing a positive relationship between Hcy levels and N-desmethyl-olanzapine concentration that is one of the main olanzapine metabolites (Lu et al, 2013 ). These inconsistent results might be attributed to heterogenous methodology such as the recruitment of different patients defined by illness duration or symptomatic presentation, as well as the lack of adjustment for possible confounders including the MTHFR genotype, dietary habits, cigarette smoking or other known factors influencing Hcy metabolism.…”
Section: Homocysteine In Psychiatric Disordersmentioning
confidence: 99%
“…Another cross-sectional study revealed no significant difference in Hcy level between schizophrenia patients receiving clozapine in monotherapy and healthy controls (Wysokiński and Kłoszewska, 2013 ). There is also one study showing a positive relationship between Hcy levels and N-desmethyl-olanzapine concentration that is one of the main olanzapine metabolites (Lu et al, 2013 ). These inconsistent results might be attributed to heterogenous methodology such as the recruitment of different patients defined by illness duration or symptomatic presentation, as well as the lack of adjustment for possible confounders including the MTHFR genotype, dietary habits, cigarette smoking or other known factors influencing Hcy metabolism.…”
Section: Homocysteine In Psychiatric Disordersmentioning
confidence: 99%
“…This study used modified high-performance liquid chromatography (HPLC) coupled with electrochemical detector as described in our previous study [ 21 ], except that 80 mM phosphate buffer (NaH 2 PO 4 ) was used to enhance system stability and LC-MS-grade acetonitrile was used to minimize noise. Patients meeting the inclusion criteria (aged 18–60 years, stable OLZ dose for at least three months, and full capacity to consent) were recruited according to the methodology of Lu et al [ 21 ]. This study, including its procedures, was approved by the institutional review board and the ethics committee of Taipei Medical University (Approval No.…”
Section: Methodsmentioning
confidence: 99%
“…The SPE procedure was modified from the study of Lu et al, 13 and a new strata-X cartridge (30 mg, 1 mL; Phenomenex Inc, Torrance, California) was used. The extraction procedure is briefly described as follows: after the cartridges were activated and conditioned, 0.2 mL of patients' plasma or blank plasma (free of DEFR or…”
Section: Determination Of Defr and The Defr Iron Complexmentioning
confidence: 99%
“…The precision and accuracy were expressed as previously described. 13 Each spiked sample was obtained using the extraction procedure described above. The %CV for each tested concentration from the calibrators, spiked with DEFR (3.21, 9.64, 16.07, 32.14, 96.41, and 192.8 μmol/L), Fe-(DEFR) 2 (0.38, 1.13, 1.88, 3.76, 11.27, and 22.54 μmol/L), and IS (94.68 μmol/L) or a blank were all o15%.…”
Section: Assay Validationmentioning
confidence: 99%